Futebol feminino e o pequeno jogo: demandas física e fisiológica de alta intensidade - Renan Renato Cruz dos Santos (2023)
Training with the small-sided games (SSG), integrating the physical, physiological, technical and tactical components present in the formal game, is widely used in the routines of clubs at the most diverse levels. Although the physical and physiological demands are already well characterized in male football athletes, little has been done regarding women's football. Aiming to investigate the physical and physiological demands of high intensity SSG with different configurations in female football athletes, this thesis is organized into 3 studies with different experimental designs and objectives, namely: (i) study 1 – compare the physical and physiological demands high-intensity SSG with different formats (3vs.3 and 5vs.5) in female football athletes; (ii) study 2 – compare the physical and physiological demands of high intensity in SSG 5vs.5 with different relative areas (≈75m² - 175m² - ≈275m²) in female football athletes, and; (iii) study 3 – compare the physical and physiological demands of high intensity in SSG 5vs.5 with continuous (1 set of 16min) and intermittent regimes (4 sets of 4min with 4min breaks and 8 sets of 2min with 2min breaks) with equivalent stimulus:pause ratios (1:1) in female football athletes. The main conclusions of the studies were: i) In study 1, the results demonstrated that PJ 3vs.3 presents greater high-intensity physical and physiological demands than 5vs.5 SSG in female football players. Considering that the main variables that presented differences for physical demand refer to actions to change speed and/or direction (e.g., accelerations and decelerations) and, for physiological demand, the time spent in the zone above 90% peak heart rate and rating perceived exertion; ii) In study 2, the evidence indicated a greater physical demand in SSG applied in a relative area per player greater than 100m² than SSG with a smaller size. On the other hand, for physiological demand, no differences were found in the different field sizes investigated; iii) In study 3, it was verified that among the intermittent SSG applied, there were no differences regarding high-intensity physical and physiological demands. Otherwise, SSG with a continuous regime presented greater physiological demand than intermittent regimes. The results obtained in the studies that make up this thesis can be used to develop conditioning programs using SSG in women's football.